SCN5A Nonsense Mutation and NF1 Frameshift Mutation in a Family With Brugada Syndrome and Neurofibromatosis - Micaglio, Emanuele; Monasky, Michelle M.; Ciconte, Giuseppe; Vicedomini, Gabriele; Conti, Manuel; Mecarocci, Valerio; Giannelli, Luigi; Giordano, Federica; Pollina, Alberto; Saviano, Massimo; Crisà, Simonetta; Borrelli, Valeria; et al. (Frontiers in Genetics, 2019)
In this case series, we report for the first time a family in which the inherited nonsense mutation [c. 3946C>T (p.Arg1316*)] in the SCN5A gene segregates in association with Brugada syndrome (BrS). Moreover, we also report, for the first time, the frameshift mutation [c.7686delG (p.Ile2563fsX40)] in the NF1 gene, as well as its association with Type 1 Neurofibromatosis (NF1), characterized by pigmentary lesions (café au lait spots, Lisch nodules, freckling) and cutaneous neurofibromas. Both of these mutations and associated phenotypes were discovered in the same family. This genetic association may identify a subset of patients at higher risk of sudden cardiac death who require the appropriate electrophysiological evaluation. This case series highlights the importance of genetic testing not only to molecularly confirm the pathology, but also to identify asymptomatic family members who need clinical examinations and preventive interventions, as well as to advise about the possibility of avoiding recurrence risk with medically-assisted reproduction.